Stoichiometry in Chemistry as a Reflection of the Values of the Qur'an - Muhammad Habib Ash Shiddiqi; Jaslin Ikhsan; Muhaimin Muhaimin; Dyah Purwaningsih; Mizzan Ayubi (SERUMPUN : Journal of Education, Politic, and Social Humaniora, 2025)
This research explores the integration of Islamic values in chemistry education, particularly focusing on stoichiometry. Stoichiometry, a key concept in chemistry that emphasizes balance and proportionality, is aligned with the principles of justice and balance as highlighted in the Qur'an. The study aims to analyze how these scientific principles reflect Qur'anic values and how they can be applied in educational settings. A descriptive qualitative method was employed, utilizing library research to gather data from chemical literature and Qur'anic commentaries. The research found significant parallels between the laws of stoichiometry and the Qur'anic teachings on balance, precision, and order in creation. Verses such as Surah Ar-Rahman (55:7-9) emphasize maintaining balance, which mirrors the necessity of balance in chemical reactions. The study concludes that integrating these values into chemistry education can provide a holistic understanding of science, reinforcing both religious and scientific perspectives.